Exploring pH-Responsive Color Changes of Anthocyanin Extracts from Four Selected Plants as Potential Natural Food Deterioration Indicators - Jusnita, Nina; Sugiyono, Sugiyono; Yuliana, Nancy Dewi; Suyatma, Nugraha Edhi (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Anthocyanins are natural pigments known for their pH sensitivity, resulting in distinct chemical structures and color changes across different pH levels. This study investigated the potential of anthocyanin-rich extracts from four plant sources, namely Antidesma bunius (L.) Spreng fruit extract (AE), Syzygium cumini fruit extract (SE), Hibiscus x archeri Wats. flower extract (HE), and Etlingera hemisphaerica flower extract (EE) as natural indicators for food deterioration. The extracts were evaluated for total anthocyanin content (TAC), antioxidant activity (as DPPH radical scavenging), antibacterial activity (via disk diffusion), and pH sensitivity based on visible color changes across a pH range of 2–12. Among the tested samples, HE exhibited the highest TAC (88.89 ± 1.40 mg C3G/g extract) and antioxidant activity (25.46 ± 1.62 mg AEAC/g extract). HE (50%) demonstrated promising antibacterial inhibition against A. hydrophila, S. typhimurium, and L. monocytogenes, with inhibition zones of 9.07 ± 0.49 mm, 9.04 ± 1.12 mm, and 10.19 ± 0.80 mm, respectively. Moreover, HE demonstrated clear, visually perceptible color transitions across pH levels, supported by variations in ΔE and oHue. The ΔE value increased from 3 at pH 3 to 9.55 at pH 8, while oHue value shifted from 36.63 o to 345.96o. This significant change is linked to the extract’s clear colour transition, which is red at pH 3-6, purple at pH 7, and red-purple at pH 8. These results demonstrate the HE as a promising candidate for pH indicator of food deterioration monitoring, as evidenced by its sensitivity to pH fluctuation among the tested extracts.